Enjoy pigeonpea pods for vegetable - Rai, A K; Khajuria, S; Lata, Kanak; Joshi, H K (Indian Horticulture, 2015)
The pigeonpea crop is mainly cultivated as pulse crop (dried seed) but it is suggested to cultivate pigeonpea for vegetable purpose (harvesting pods for green seed). The pigeonpea can be easily grown in semi-arid region. The vegetable pigeonpea is more nutritive, easily digestible and tasteful, and easy to cook. It gives more yield from unit area. It is harvested earlier than the seed crop and fetches good price.